2016
DOI: 10.1038/ncomms12493
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of TGFβ receptors in stem cells drives cutaneous squamous cell carcinoma

Abstract: Melanoma patients treated with oncogenic BRAF inhibitors can develop cutaneous squamous cell carcinoma (cSCC) within weeks of treatment, driven by paradoxical RAS/RAF/MAPK pathway activation. Here we identify frequent TGFBR1 and TGFBR2 mutations in human vemurafenib-induced skin lesions and in sporadic cSCC. Functional analysis reveals these mutations ablate canonical TGFβ Smad signalling, which is localized to bulge stem cells in both normal human and murine skin. MAPK pathway hyperactivation (through BrafV60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 72 publications
(118 reference statements)
7
92
1
Order By: Relevance
“…Given the histological and mutational similarities including deregulated TGFβ signaling in progressed mouse and human SCCs (Cammareri et al, 2016; Cancer Genome Atlas Network, 2015; Lu et al, 2006; McCreery et al, 2015; Nassar et al, 2015), we compared transcriptomes of HPV-negative HNSCCs that showed either a complete response or resistance to carboplatin or cisplatin (P) followed by paclitaxel (T) (Cancer Genome Atlas Network, 2015). Unsupervised cluster and principle component analyses revealed clear differences between patients presenting with either progressive disease or a complete response (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Given the histological and mutational similarities including deregulated TGFβ signaling in progressed mouse and human SCCs (Cammareri et al, 2016; Cancer Genome Atlas Network, 2015; Lu et al, 2006; McCreery et al, 2015; Nassar et al, 2015), we compared transcriptomes of HPV-negative HNSCCs that showed either a complete response or resistance to carboplatin or cisplatin (P) followed by paclitaxel (T) (Cancer Genome Atlas Network, 2015). Unsupervised cluster and principle component analyses revealed clear differences between patients presenting with either progressive disease or a complete response (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of RII or LGR5 would decrease TGFβ signaling, enabling colon cancer cells to escape TGFβ tumor suppressor function. In addition to colon cancer, studies in squamous cell carcinoma (SCC) show that inactivation of TGFβ receptors coupled with hyperactivation of RAS/RAF/MAPK signaling or Tp53 mutation in LGR5 + stem cells drives rapid development of cutaneous SCC (49), suggests that TGFβ signaling inactivation could be a tumor-initiating event. These studies provide compelling support for the tumor suppressive role of TGFβ signaling in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis was argued against by the authors of a case series confirming that SCC develop in RDEB patients even when COL7 is totally absent in the patients' skin and by the presence of COL7‐null SCC. Indeed, mutations in Hras are not prevalent, while the genes encoding Notch, p53 and p16 are frequently mutated in RDEB‐SCC cell lines, as well as in sporadic SCC and other SCC cell lines . To date, no major differences in gene expression (except COL7A1 ) have been reported between RDEB‐SCC and non‐RDEB‐SCC cells, except in SLCO1B3 , which encodes the liver‐specific organic anion transporter polypeptide OATP1B3.…”
Section: Col7 In Wound Healing and Carcinogenesis Of Keratinocytesmentioning
confidence: 99%